“AN EMPIRICAL EVIDENCE OF INTERNATIONAL PORTFOLIO DIVERSIFICATION IN EMERGING MARKETS NAMELY 2 ASIAN POWER HOUSES INDIA AND CHINA TO THE U.K. INVESTOR’S’’ - Gutha rajashekar, swathi (2015)
This paper studies, the relationship of long-term and short-term between the U.K. stock market and two top Asian emerging markets, which is India and China. From the correlation coefficient, it is found there are low short-term correlations between these Asian emerging markets and the U.K. The unit root test is used to determine the existence of non-stationarity in the time series data. The results of Augmented Dickey Fuller test and Phillips Perron test shows there is existence of non-stationarity in the time series index data. The Johansen cointegration method of bilateral and multilateral indicates that there is no long-term relationship among these stock markets. Then the Granger-causality test is applied in order to determine the short-term relationship. This test is used because we find no evidence of long-term relationship. The Granger’s Causality test does reveal causality running from the China to U.K. market and India to U.K. market, but none from the U.K. market. Therefore, it shows there is no short-term relationship between U.K. and the Asian emerging market. Overall, the results from all the tests from our data suggest that U.K. investors can have gains from international portfolio diversification when they invest into these Asian emerging markets.